Style consumption and propensity to indebtedness: evidence on the peace border - Mendonça Flores, Silvia Amélia; Bidarte, Marcos Vinicius Dalagostini (Revista de Administração da UFSM, 2019)
This research has investigated behavioral factors and demographic variables in the propensity for debt in Santana do Livramento, Brazil and Rivera, Uruguay. The data was collected through a structured questionnaire with quantitative scales for the debt, materialism, perception and risk behavior and other profile issues. In relation to the debt, the central theme of the research, it is perceived that the respondents have submitted a more conservative behavior as it pertains to propensity to incur debts, presenting a high risk perception and a more conservative behavior risk. In relation to materialism, the respondents demonstrated a tendency to purchase goods to satisfy their wishes. This result can be associated with the profile of the Peace Border that occurs due to the diversity of imported products aligned to shopping tourism incentive. We also emphasize that aspects that can influence individuals in the propensity for debt are the 'perception of risk' and the demographic variable 'age'. This research has investigated behavioral factors and demographic variables in the propensity for debt in Santana do Livramento, Brazil and Rivera, Uruguay. The data was collected through a structured questionnaire with quantitative scales for the debt, materialism, perception and risk behavior and other profile issues. In relation to the debt, the central theme of the research, it is perceived that the respondents have submitted a more conservative behavior as it pertains to propensity to incur debts, presenting a high risk perception and a more conservative behavior risk. In relation to materialism, the respondents demonstrated a tendency to purchase goods to satisfy their wishes. This result can be associated with the profile of the Peace Border that occurs due to the diversity of imported products aligned to shopping tourism incentive. We also emphasize that aspects that can influence individuals in the propensity for debt are the 'perception of risk' and the demographic variable 'age'.